METHODOLOGIES FOR MANAGING THE TREEFALL RISK OF URBAN TREES - Emerick, Tamilis; Martini, Angeline; Bhering, Leonardo (Floresta, 2024)
Recently, concern about the risk of falling trees, triggered by several fatal accidents involving falls in urban environments, has increased the interest of managers around the world in developing effective assessment techniques for accident prevention. The objective of this study was to compare different methods of visual assessment of the risk of falling urban trees in Spathodea campanulata individuals. To do so, 43 individuals were analyzed using five visual risk analysis methodologies. Data collection was conducted between December/2020 and January/2021 using a form created in Google Forms. The risk level classification was standardized into high, medium and low for all methodologies, and statistical tests were performed to verify the similarity between them. The time taken for analysis was timed and tree DBH dimensions were measured to verify the correlation with the degree of risk. It was observed that 41.8% of the trees were included in the high-risk class by all methodologies, with methodology II showing the lowest variation between individuals. Statistically, methodology I differed from all methodologies, while II was only the same as IV, and the others were similar. AV is the fastest and I takes the longest. No high correlation was found between time spent and degree of risk of falling trees or DBH.